Frankenstein - Gray, Elizabeth
"Frankenstein, for that is your name, isn't it? Or should I call you father? Call me what you like. Why did you bring me into this world of hate, Frankenstein? I was surprised by how well he spoke. It is not a world of hate. It is a world of love... Love? What is love? You have shown me no love. The world has shown me nothing but hate..."